(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Researches of the pathological states of the surface tissues of the eyeball to date remain relevant. Objective. To study the state of the thiol system redox potentials in the cornea in experimental keratitis on the background of diabetes progression Material and methods. To conduct the experiments 52 rabbits were used. They were divided into three groups: the first was the control group (8 rabbits), the second was the experimental group of animals with keratitis (23 rabbits), the third was the experimental group of animals with keratitis on the background of the streptozotocin-induced diabetes (22 rabbits). In the corneal tissue the definition of reduced and oxidized glutathione was performed. Results. In conditions of the progression of experimental keratitis and streptozotocin-induced diabetes, the reduction of the restored glutathione level and the increase of the oxidized glutathione level in the tissue of the cornea were determined. Conclusions. 1. Under the conditions of keratitis progression, the glutathione status disruption in the tissues of the cornea is expressed in animals with diabetes more significantly. The level of the restored glutathione was reduced comparing to animals with keratitis without non-streptozotocin-induced diabetes by 11.4 % during the first period, and by 18.0 % during the second period, and by 25.5 % during the third period. 2. In the progression of the experimental keratitis and streptozotocin-induced diabetes, the increase of oxidized glutathione in the cornea was observed. In different observation periods in such conditions, the concentration of the oxidized glutathione in the cornea has increased by 7.1%, 10.1% and 20.0%.